HUBUNGAN PELAYANAN POSYANDU LANSIA DENGAN TINGKAT KEPUASAN LANSIA DI WILAYAH KERJA PUSKESMAS SUKORAMBI KABUPATEN JEMBER - Dony Setiawan Hendyca Putra (Jurnal Kesehatan dr. Soebandi, 2013)
Elderly posyandu is an integrated service post for the community elderly in a certain areas that have been agreed, which is driven by the community where they can get health care. The design of this study using a descriptive cross-sectional correlative approach, with variable levels of service satisfaction posyandu elderly and elderly. The population in this study is the elderly who live in the Village I Village Sukorambi Krajan RW Sukorambi Jember District. Lansianya amount is 127 people. The sampling technique used was simple random sampling techniques (simple random sampling). The samples used were as many as 96 elderly people by using simple random sampling technique sampling. Retrieval of data using a questionnaire enclosed with the form of answers to a graduated scale, which is measured at the time of completion of the activity in the elderly posyandu elderly. Based on the analysis of the data processed using spearman rho showed a direct relationship between service satisfaction levels posyandu elderly by the elderly in Hamlet Krajan Work Area Health Center Sukorambi Jember with p-value 0.000. The conclusion of this study is that there is a relationship posyandu elderly with satisfaction levels in elderly Hamlet Village Krajan RW I Sukorambi Work Area Health Center Sukorambi Sukorambi Jember District. Recommendations of this study is posyandu seniors who routinely carried out 1 time a month, can be applied in elderly health care in posyandu elderly.